An Evaluation of Ovine Shelters and Hovels in terms of Settlement and Rural Housing in Dosemealti District of Antalya - İhsan Bulut; Berna Özoğul; Burak Manav; Metehan Kurtlu (Coğrafya Dergisi)
Rural settlements and dwellings are one of the most discussed subjects in human geography. They are one of the subjects that demonstrate little change over a long time in terms of definitions, naming, and qualities, but however, greatly vary over short distances. This study highlights the attributes of the sheepcote (yatak) settlements in the Dosemealti district of Antalya province, and analyzes the importance of sheepcotes for rural settlement. The study aims to reveal the functional features of the sheepcote settlements in the region, the factors affecting the selection of the establishment site, the materials used, and the actions in the sheepcotes. Qualitative research methods were used in the study, and field research, interview, and document analysis studies were carried out. Primarily, the relevant literature was reviewed, and later field studies at different times were conducted; detailed interviews were conducted with sheepcote owners, who were found to have been using sheepcotes for sheep and goat farming activities for years. The sheepcotes’ distribution determined in field studies was mapped using the ArcGIS 10.4.1 program.